Harmonic source localization method for the port distribution system based on the stagewise regularized orthogonal matching pursuit algorithm - Yang, Ruixiang; Yu, Moduo; Tai, Nengling; Duan, Ruochen; Lu, Chao (Frontiers in Energy Research, 2023)
The application of power electronic technology which is widely used in large mechanical equipment of ports causes inevitable harmonic pollution issues. Due to the small capacity of the port power system, harmonic interference will bring huge security risks to its normal operation. Therefore, it is necessary to carry out the effective localization of the harmonic sources in the grid. In this paper, a harmonic source localization method based on the stagewise regularized orthogonal matching pursuit (SROMP) is proposed by improving the orthogonal matching pursuit (OMP) in a compressed sensing theory. It can achieve accurate localization of harmonic sources only through measurement information analysis, which is significantly superior to traditional methods. First, according to the grid topology and line parameters, a system equation is constructed that takes the node harmonic voltage as the measurement variable and the harmonic current injected to the node as the state variable. Next, the equation is solved to obtain the harmonic current value injected to each node. The result can reflect the harmonic injection situation of each node, so as to determine the position of each harmonic source. In order to test the localization effect of the algorithm under different measurement configurations, the SROMP method is compared with other algorithms in considerable simulation experiments on the improved IEEE-33 model, which verifies the stability and accuracy of the proposed algorithm.